Attention Mechanisms Evaluated on Stenosis Detection using X-ray Angiography Images - Ovalle-Magallanes, Emmanuel; Alvarado-Carrillo, Dora E.; Avina-Cervantes, Juan Gabriel; Cruz-Aceves, Ivan; Ruiz-Pinales, Jose; Contreras-Hernandez, Jose Luis (Journal of Advances in Applied & Computational Mathematics, 2022)
Coronary stenosis results from unnatural narrowing of the heart arteries due to the accumulation of adipose depots, leading to different heart diseases and yielding top mortality worldwide. Thus far, deep learning-based methods for automatic stenosis over X-ray Coronary Angiography (XCA) have employed state-of-the-art architectures to solve the ImageNet challenge. With the advance of deep learning, contemporary architectures incorporated a variety of attention mechanisms to improve performance. Therefore, this paper presents a study of three attention mechanisms for stenosis detection in XCA images. Extensive experiments and comparisons over different Residual backbone networks are presented to verify the effectiveness of including such attention modules. An improvement of 4%, 10%, and 10% on the accuracy, recall, and F1-score was achieved using the approach, reaching mean values of 0.8787, 0.8610, and 0.8732, respectively.